BORED PILE FOUNDATION AND DIAPHRAGM WALL DESIGN OF RENT OFFICE BUILDING IN SERPONG - RAKHA AMMAR (NIM : 15013010), DIMAS
The office buliding consists of 16-storey tower, 3-storey podium, and 4-storey basement. Therefore, pile foundation and retaining wall is needed to support building structures. Pile foundation is used to bear upper structures load and retaining wall is applied to protect basement excavation. The first step of retaining wall design is to determine the preliminary of depth of penetration. After that, the retaining wall and excavation stages calculated using PLAXIS 2D with ground anchor installation. The final step is to check basal heave and dewatering calculation. Axial capacity of single pile calculated using Skempton and Reese& Wright formula with three different pile diameter (800 mm, 1000 mm, and 1200 mm). Next step is calculate the efficiency of group pile using Converse-Labare, Los Angelese, and Seiler-Keeney method, so the most efficient pile diameter can be determined. Lateral capacity of single pile calculated using Lpile. Internal forces of each piles calculated using Group. The settlement of piles calculated using raft equivalent method.